Kinematic analysis of Australian elite seated shot-putters during the 2002 Ipc World Championship: Parameters of the shot`s trajectory - Frossard, L. A.; Schramm, A. J.; Goodman, S. (Proceedings International Society of Biomechanics XIXth Congress. The Human Body in Motion, 2003)
A total of 3 male elite shot-putters members of the Australian team participated to this study (Table 1). The video recording of all their attempts was conducted during the 2002 IPC World Championships using a digital video camera filming a 25 Hz. The camera was positioned perpendicularly to the frame on the ground, used to secure the athlete`s seat, at 1.6 m high and 16 m on the right side of the thrower. The field of view of the camera included at the bottom the full-length (2.29 m) and full-width (1.68 m) of the plate. It was also enlarged in the direction of the put to secure the recording of at least the ten first frames of the shot`s aerial trajectory. The video data was digitized and the displacements of shot in the sagittal plane were pointed manually frame-by-frame at 50 Hz around the instants of release. The origin of the global coordinate system (GCS) was located at the point on the frame from where the officials measured the performance. The value of the parameters of the shot`s trajectory for the best attempt of each athlete was presented in Table 1. All these values were expressed in the GCS, consequently, a positive value of the position along the antero-posterior axis indicated that the thrower released the shot ahead of the point of measurement of the performance. The parameters of the shot`s trajectory, particularly the velocity of the shot at the instant of release, for the best attempt of three Australian elite athlete are presented. It is hoped that this paper will provide valuable information to those concerned with the actual performance of elite seated shot-putters during world-class competition, such as athletes, coaches, classifiers and referees.